The Mystery of Skepticism : New Explorations - McCain, Kevin,; Poston, Ted, (Brill Studies in Skepticism, 2019)
The Mystery of Skepticism: New Explorations represents the cutting-edge of research on underexplored skeptical challenges, dimensions of the skeptical problematic, and responses to various kinds of skepticism. The thirteen newly commissioned essays, edited by Kevin McCain and Ted Poston, demonstrate that despite its long history philosophical reflection on skepticism and the challenges it poses is alive and well. The essays in The Mystery of Skepticism enhance our understanding of skepticism by breathing new life into old debates and sparking new ones. The Mystery of Skepticism will shape discussions of skepticism for years to come.